2021
DOI: 10.1111/jocd.14254
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of death and survival cervical necrotizing fasciits cases

Abstract: Background Cervical Necrotizing Fasciitis (CNF) is associated with a high mortality rate. The occurrence of mediastinitis with CNF may increase mortality up to 70%. Aims We aimed to identify the differences between surviving and deceased cases. Methods The present study was conducted retrospectively by scanning the files of 16 patients between the ages of 19–71 who were diagnosed with CNF. Patients were divided into two groups as the surviving patient group (SPG) and the deceased patient group (DPG). Both grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…In this study, an antimicrobial sensitivity test was taken, with the most sensitive results being Tigecyline (69.65%), followed by Meropenem (56.5%), Amikacin (52%), Gentamicin (39.1%), and Cefepime (39.1%). In the examination of antibiotic resistance, it was found that the types of antibiotics were resistant to CNF patients, the antibiotic Cefazolin gave the most resistance to 17 cases (73.91%), Ceftriaxone to 16 cases (69.59%) of CNF (Sizer, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, an antimicrobial sensitivity test was taken, with the most sensitive results being Tigecyline (69.65%), followed by Meropenem (56.5%), Amikacin (52%), Gentamicin (39.1%), and Cefepime (39.1%). In the examination of antibiotic resistance, it was found that the types of antibiotics were resistant to CNF patients, the antibiotic Cefazolin gave the most resistance to 17 cases (73.91%), Ceftriaxone to 16 cases (69.59%) of CNF (Sizer, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Adequate intensive care is important to maintain the patient's normal metabolic processes, fluid, and electrolyte substitution. Unfortunately, in some cases, septic shock can occur, which can cause damage to multiple organs and lead to lethal outcomes (Sizer, 2021).…”
Section: Discussionmentioning
confidence: 99%